2018
DOI: 10.1016/j.jmaa.2018.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Generalized harmonic morphisms and horizontally weakly conformal biharmonic maps

Abstract: Harmonic morphisms are maps between Riemannian manifolds that pull back harmonic functions to harmonic functions. These maps are characterized as horizontally weakly conformal harmonic maps and they have many interesting links and applications to several areas in mathematics (see the book [2] by Baird and Wood for details). In this paper, we study generalized harmonic morphisms which are defined to be maps between Riemannian manifolds that pull back harmonic functions to biharmonic functions. We obtain some ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…They give a characterisation of these objects between Riemannian manifolds. In general this is rather complicated, see Theorem 2.2 of [4]. In our context, of complex-valued functions, it is the following.…”
Section: Theorem 32 a Complex-valued Functionmentioning
confidence: 92%
See 2 more Smart Citations
“…They give a characterisation of these objects between Riemannian manifolds. In general this is rather complicated, see Theorem 2.2 of [4]. In our context, of complex-valued functions, it is the following.…”
Section: Theorem 32 a Complex-valued Functionmentioning
confidence: 92%
“…In their paper [4], the authors introduce the notion of generalised harmonic morphisms between Riemannian manifolds. These are exactly the (2, 1)-harmonic morphisms in the sense of our Definition 2.4.…”
Section: Theorem 32 a Complex-valued Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper [5], the authors found many examples of biharmonic Riemannian submersions in their study of generalized harmonic morphisms which are maps between Riemannian manifolds that pull back local harmonic functions to local biharmonic functions.…”
Section: Introductionmentioning
confidence: 99%
“…is a proper biharmonic Riemannian submersion with the mean curvature vector field of fibers being basic vector field. In fact, using cylindrical coordinates (r , θ, ϕ, x 4 ) the Riemannian submersion can be expressed as φ(r , θ, ϕ, Example 2 (see [5] for details) Let R 2 + = {(x, y) ∈ R 2 : y > 0} denote the upper-half plane and C be a positive constant. Then, the Riemannian submersion defined by the projection of the warped product…”
Section: Introductionmentioning
confidence: 99%